Nano-size boron carbide intercalated graphene as high performance catalyst supports and electrodes for PEM fuel cells. (July 2016) - Mu, Shichun; Chen, Xu; Sun, Ronghui; Liu, Xiaobo; Wu, Hui; He, Daping; Cheng, Kun
Abstract: The low utilization and stability of noble-metal catalysts is always a big barrier to commercialize proton exchange membrane (PEM) fuel cells. Here we report a positive progress on stabilizing the catalyst by modulating 2D graphene as an advanced support of Pt nanoparticles, where the interlayer of graphene is near perfectly intercalated by nano-B4 C ceramics. The strong restriction effect of nano-ceramics in graphene interlayers, can greatly improves the usage and electrochemical stability of Pt catalysts. As results, our new graphene/B4 C supported Pt catalyst (Pt-RGO/B4 C) shows greatly enhanced electrochemical surface area (121 m 2  g −1 ) and mass activity (185 A g −1  Pt) towards oxygen reduction reaction (ORR), which is remarkably higher than the reduced graphene oxide (RGO) supported Pt (Pt/RGO) catalyst and the commercial Pt/C catalyst. In addition, the Pt-RGO/B4 C electrode also possesses higher fuel cell performance than the Pt/RGO electrode. Especially, after the electrochemical acceleration test for 10000 cycles, our new catalyst presents an excellent stability, even retains 45.2% initial electrochemical surface area, while the Pt/RGO and Pt/C are only 29.7 and 23.4%, respectively. These indicate our unique catalyst is promising to allow the PEM fuel cell have high ORR activity and stability.